A-97 Headache before and after Mild Traumatic Brain Injury: Acute-to-Subacute Outcomes in Patients with no Headache, Pre-Existing Headache, and Post-Traumatic Headache. (30th August 2021) - Karr, Justin E; Williams, Michael W; Iverson, Grant L; Huang, Sheng-Jean; Yang, Chi-Cheng
Abstract: Objective: Patients who experience a mild traumatic brain injury (MTBI) may have a headache condition preceding injury, develop a post-traumatic headache after injury, or experience headache neither before nor after injury. This study examined whether MTBI patients with no headache, pre-existing headache, and post-traumatic headache differed in acute-to-subacute outcomes. Method: Patients with MTBI were recruited from an outpatient neurosurgery clinic in Taipei, Taiwan after emergency department referral (N = 291; 40.2% men; M = 37.9 ± 13.9 years-old; Mdn = 7 days-since-injury, range = 0–21), completing neuropsychological tests of attention, memory, and verbal fluency and questionnaires evaluating depression, anxiety, and post-concussion symptoms. Participants with no headache (reported neither pre- or post-injury), pre-existing headache (reported pre-injury headache, of whom some reported worsened post-injury headache), and post-traumatic headache (denied pre-injury headache, reported post-injury headache) were compared using non-parametric ANCOVA, controlling for gender and days-since-injury. Results: Neuropsychological test performances did not differ between headache groups. Participants with pre-injury headache and post-traumatic headache had greater change in self-reported physical (F = 25.52, p < 0.011, η2 = 0.15) and cognitive symptoms (F = 3.74, p = 0.025, η2 = 0.03) than participants with no headache. Participants with pre-injury headache reported worse post-injury anxiety symptoms than participants with post-traumatic headache (F = 12.02, p < 0.011, η2 = 0.08). Conclusion(s): Participants with pre-injury and post-traumatic headache did not differ in outcome within 21 days of injury but had worse self-reported physical and cognitive symptoms than participants with no headache. Most participants with pre-injury headache experienced worsened headache following MTBI (53.7%). Future research is needed to assess whether more specific headache subtypes are differentially associated with MTBI outcome.